Pendampingan Penggunaan AI Dan Peningkatan Penulisan Artikel Ilmiah Dalam Pembelajaran BI - Istiqomah, Fina Zaidatul; Manshur, Ali (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to interpret the mentoring process in utilizing Artificial Intelligence (AI) to improve scientific article writing skills in Indonesian language learning. The research employed Participatory Action Research (PAR) conducted through four stages: (1) Planning, which involved identifying students’ needs and designing training programs; (2) Action, which included technical training, writing practice, and article clinics; (3) Observation, focusing on participation, challenges, and skill development; and (4) Reflection, carried out through joint evaluation between mentors and students. The findings reveal that AI integration effectively supports students in enhancing grammar, text structure, citation management, and access to academic literature, while human mentoring plays a crucial role in fostering critical thinking, maintaining originality, and ensuring compliance with publication ethics. The implication highlights that the synergy between digital technology and pedagogical mentoring is highly effective in strengthening students’ academic literacy and preparing them for the demands of scientific publication in the digital era.